2000
DOI: 10.1016/s0735-1097(00)00933-5
|View full text |Cite
|
Sign up to set email alerts
|

Losartan, an angiotensin type 1 receptor antagonist, improves endothelial function in non-insulin-dependent diabetes

Abstract: Losartan administration at 50 mg per day improved endothelium-dependent dilation of resistance vessels in patients with NIDDM. That is, blockade of the angiotensin II type 1 receptors improves endothelial function in NIDDM. At least some of the similarly beneficial effect of ACE inhibition is probably mediated also through the angiotensin II-type 1 receptor pathway. The use of a type 1 receptor antagonist seems a reasonable alternative to an ACE inhibitor to maintain endothelial function in NIDDM subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
95
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(97 citation statements)
references
References 28 publications
0
95
1
1
Order By: Relevance
“…Under diabetic conditions, the renin-Ang system is activated and vascular AT1R expression is enhanced, 11,22 thereby contributing to diabetes mellitus-associated endothelial dysfunction. 12 Given the known vascular (endothelial)-protective effects of HDL, [13][14][15] we hypothesized that HDL could also regulate vascular AT1R expression under diabetic conditions and could thereby influence Ang II-mediated signaling. To investigate this hypothesis, we increased HDL in vivo via human apo A-I gene transfer, leading to hepatocyte-specific human apo A-I expression in STZ-induced diabetic rats and supplemented HDL to HAECs under HG in the presence or absence of Ang II.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under diabetic conditions, the renin-Ang system is activated and vascular AT1R expression is enhanced, 11,22 thereby contributing to diabetes mellitus-associated endothelial dysfunction. 12 Given the known vascular (endothelial)-protective effects of HDL, [13][14][15] we hypothesized that HDL could also regulate vascular AT1R expression under diabetic conditions and could thereby influence Ang II-mediated signaling. To investigate this hypothesis, we increased HDL in vivo via human apo A-I gene transfer, leading to hepatocyte-specific human apo A-I expression in STZ-induced diabetic rats and supplemented HDL to HAECs under HG in the presence or absence of Ang II.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, diabetes mellitus was induced by a single injection of streptozotocin (STZ; 70 mg/kg; IP) in 8-week-old male Sprague-Dawley (SD) rats. Five days after STZ injection, IV gene transfer with 3ϫ10 12 particles per kg of the E1E3E4-deleted adenoviral vector Ad.hapo A-I, which induces hepatocyte-specific expression of human apo A-I in the absence of significant hepatotoxicity, 21 or of the control vector Ad.Null, which contains no expression cassette, 21 was performed. Six weeks after gene transfer, rats were euthanized, and endothelium-dependent vasorelaxation was determined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More intriguingly, the combined chronic treatment with enalapril and losartan increased ACh-induced as well as basal plasma NO concentration significantly more than either enalapril or losartan alone. Several clinical studies have demonstrated that both ACEIs and ARBs improve endothelial function in patients with cardiovascular risk factors or coronary disease (10)(11)(12). However, in those studies endothelial function was quantified by measuring secondary effects of NO, such as biologically inactive products of NO (nitrite and nitrate) or flow-dependent endothelium-mediated vasodilation.…”
Section: Discussionmentioning
confidence: 99%
“…In several clinical studies, both angiotensin-converting enzyme (ACE) inhibitors (ACEIs) and angiotensin type 1 (AT1) receptor blockers (ARBs) have been shown to improve endothelial function in patients with cardiovascular risk factors or coronary disease (10)(11)(12). However, the effects of these agents on the bioavailability of NO and vascular remodeling has not been investigated in details.…”
Section: Introductionmentioning
confidence: 99%